2014
DOI: 10.1002/cssc.201300723
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen‐Bond‐Assisted Activation of Allylic Alcohols for Palladium‐Catalyzed Coupling Reactions

Abstract: We report direct activation of allylic alcohols using a hydrogen-bond-assisted palladium catalyst and use this for alkylation and amination reactions. The novel catalyst comprises a palladium complex based on a functionalized monodentate phosphoramidite ligand in combination with urea additives and affords linear alkylated and aminated allylic products selectively. Detailed kinetic analysis show that oxidative addition of the allyl alcohol is the rate-determining step, which is facilitated by hydrogen bonds be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Interestingly, increasing the amount of 1,3‐diethylurea for the dehydrative cross‐coupling reaction lowered the yield significantly (from 71 % (no urea) to 33 % (10 mol % urea) after 3 h; Table 1, entries 10–14). This negative effect suggests that the activation of the allyl alcohol may be different for this reaction compared to the previous reactions reported 6. Urea most likely competes for coordination with the alkene substrate, thus perhaps leading to the inhibition of the catalyst.…”
Section: Methodsmentioning
confidence: 63%
See 2 more Smart Citations
“…Interestingly, increasing the amount of 1,3‐diethylurea for the dehydrative cross‐coupling reaction lowered the yield significantly (from 71 % (no urea) to 33 % (10 mol % urea) after 3 h; Table 1, entries 10–14). This negative effect suggests that the activation of the allyl alcohol may be different for this reaction compared to the previous reactions reported 6. Urea most likely competes for coordination with the alkene substrate, thus perhaps leading to the inhibition of the catalyst.…”
Section: Methodsmentioning
confidence: 63%
“…The use of activators obviously leads to waste production, dodging any potential benefits of the direct use of allyl alcohols 5. Recently, our research group6 and those of others7 reported catalyst systems that allow the direct activation of allylic alcohols in alkylation and amination reactions without the need for stoichiometric activators. Coupling of several aliphatic and aromatic allylic alcohols with a variety of different nucleophiles has been reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The catalyst system consists Scheme 11 Allylic alcohol activation with H 2 O. 30 The catalyst system consists Scheme 11 Allylic alcohol activation with H 2 O.…”
Section: Transition Metal-catalyzed Allylic Substitution Reactions Wimentioning
confidence: 99%
“…Solvation of the hydroxyl/hydroxy moiety in the charge-developing transition state was again proposed to lower the activation energy. We recently disclosed a new phosphoramidite-based Pd(π-allyl)catalyst (1) for allylic substitution reactions, using unactivated allylic alcohols to selectively produce linear alkylated and aminated products (Scheme 1) [24]. The addition of catalytic amount of 1,3-diethylurea (3 mol%) increased the catalytic activity and improved the reproducibility of these reactions.…”
Section: Introductionmentioning
confidence: 99%